Sweetening the deal: an infodemiological study of worldwide interest in semaglutide using Google Trends extended for health application programming interface - Jacques Eugene Raubenheimer; Pieter Hermanus Myburgh; Akshaya Srikanth Bhagavathula (BMC, 2024)
Abstract Background Off-label use of semaglutide for non-diabetic weight loss (which regulators have linked to social media promotion) created worldwide supply shortages. We evaluated worldwide semaglutide interest measured by online search behavior to gauge social media and conventional print media reporting's effect on search interest. Methods Using Google Trends Extended for Health (GTEH) multiple sampling, we retrieved regional online interest (ROI) for all countries and extracted timelines and top search queries for January 2021-August 2023 for countries with median ROI ≥ 20 using the "semaglutide" topic. We obtained semaglutide media reporting from the ProQuest database. We estimated the effect of media and within-country semaglutide interest on between-country interest with Granger causality analysis. We determined changepoints for trends within each country with joinpoint regression. We determined prominent themes in search queries for each country with natural language processing thematic analysis. Results Twenty-seven countries were included. Most countries showed an increase in semaglutide interest over time, with Canada and the USA showing the largest sustained interest. Most of the search interest arose from 2022 onwards. Granger's analysis showed that media coverage could only partially explain interest, and interest in some countries partially preceded interest in others, with the UK and Germany showing strong relationships between news reports and lagged search interest. Joinpoint analysis identified up to four significant within-country changepoints. Most countries showed significant positive weekly trends in 2021-2022, although uptrends in search interest varied considerably between countries. One episode of the Dr. Oz show (TV media event) coincided with strong peaks in numerous countries. Natural language processing of top search queries showed some agreement between countries and country-specific themes. Weight loss was a major theme in most countries, while a diabetes theme was generally absent or weak. Some countries (Australia, Chile, South Africa, UK) had themes for buying Ozempic from (named) local retailers, and Germany had a theme related to buying Ozempic without a script. Conclusions GTEH data provided insights into global search interest in semaglutide and regional variation. Studies focusing on specific countries which include social media data can elucidate specific drivers behind the surge in off-label use of semaglutide.